Некоторые аспекты российско-монгольских отношений в контексте 90-летнего юбилея установления дипломатических отношений между Россией и Монголией; перспективы дальнейшего сотрудничества на многосторонней основе в рамках ШОС (Journal of International Studies, 2011)
English title: For the 90th anniversary of diplomatic relationships between Mongolia and Russia: Perspective of the bilateral cooperation among Mongolia and Russia and further development of multilateral cooperation of Shangai Cooperation Organization